2014
DOI: 10.1155/2014/896831
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Neck Abscess with Contrast-Enhanced Computed Tomography

Abstract: Neck abscesses are difficult to diagnose and treat. Currently, contrast-enhanced computed tomography (CECT) is the imaging modality of choice. The study aims to determine the predictive value of CECT findings in diagnosing neck abscess, causes of neck abscess and the most common neck space involved in the local population. 84 consecutive patients clinically suspected to have neck abscess who underwent CECT and surgical confirmation of pus were included. Demographic and clinical data were recorded. 75 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 21 publications
(55 reference statements)
0
13
0
1
Order By: Relevance
“…Regarding the effects of morphological properties of the abscess on PPV, 9 studies (39%) reported on rim enhancement ( Table 2 ) [ 8 , 14 , 16 , 18 , 19 , 21 , 24 , 26 , 30 ], and 10 studies (43%) reported on abscess diameter [ 8 , 10 , 12 , 14 , 16 , 19 , 21 , 22 , 24 , 26 ]. The meta-regression analysis found no overall effect of the moderators (CT criteria for an abscess, size of collection, rim enhancement, pediatric patients, or publication age) (p = 0.306).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the effects of morphological properties of the abscess on PPV, 9 studies (39%) reported on rim enhancement ( Table 2 ) [ 8 , 14 , 16 , 18 , 19 , 21 , 24 , 26 , 30 ], and 10 studies (43%) reported on abscess diameter [ 8 , 10 , 12 , 14 , 16 , 19 , 21 , 22 , 24 , 26 ]. The meta-regression analysis found no overall effect of the moderators (CT criteria for an abscess, size of collection, rim enhancement, pediatric patients, or publication age) (p = 0.306).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported sensitivity and specificity [ 12 , 14 , 15 , 26 , 28 , 29 ], and two additional studies reported sensitivity alone [ 20 , 23 ]. Sensitivity ranged from 0.68 to 0.99, and specificity from 0.18 to 0.63 ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perivascular and prevertebral spaces are contiguous with the upper mediastinum and pretracheal space with the anterior mediastinum. Infections affecting such spaces show a higher chance of evolving to mediastinitis [17, 18].…”
Section: Discussionmentioning
confidence: 99%